Analysis of Business Rules modeling Approaches using 4-Dimensional Business Rule Framework - Kumar Sharma, Deepak; Mahajan, Manish; Singh, Dheerendra; Praksh, Naveen (International Journal of Computer Sciences and Engineering, 2025)
Business rules could be look at different perspective in Information systems. A 4-dimensional rule framework is developed to describe rules in Business, Representation, System and Application dimension. Each dimension is laydown by a set of attributes to capture the essential characteristics of business rule. Business dimension talk about how business rule is in actual business. Representation dimensional talks about how to represent rule so that business people can easily write and understand rules. System dimension deal with the characteristics of tool developed to manage and store business rules for Business as well as Technical audience. The attributes of Application dimension describe the characteristics of executing rules in actual software system. OMG accepted a standard, namely, Semantics of Business Vocabulary and Business Rules, SBVR and claim that it is meant for business people. The authors developed a business rule model, called, Business Rules Oriented Business Model, BROBM to provide a comprehensive solution, start from the capturing business rule as see in business till the actual software application. In this paper, authors did a detailed analysis of SBVR and BROBM based on the attributes of 4-dimensional business rule framework.